Bismuth doping enhances the thermoelectric power of ZnO thin films via structural distortion modulation - Yen Binh Nguyen; Trang Thuy Thi Phan, Trieu Quang Vo; Hoa Thi Lai; Thu Bao Nguyen Le; Vinh Cao Tran; Thang Bach Phan; Anh Tuan Thanh Pham (Vietnam Journal of Science, Technology and Engineering, 2026)
The global energy conservation and pollution crisis is compelling the industry to seek methods for harvesting and conserving energy. Microfabrication methods of zinc oxide (ZnO) thin films also play a crucial role in affecting thermoelectric (TE) performance. This study investigates the TE properties of ZnO and Bi-doped ZnO thin films fabricated via radio-frequency (RF) magnetron sputtering. The incorporation of Bi into the ZnO lattice was systematically analysed to determine its impact on residual stress and electrical performance. Structural analysis confirms that Bi doping caused stress relaxation, reducing compressive stress from -1.00 to -0.36 GPa. Complementary insights from micro-Raman spectroscopy revealed Raman shifts, indicating an increase in defectrelated modes, specifically an intensified peak at 560 cm-1 associated with oxygen vacancy formation. The electrical conductivity of Bi-doped ZnO film reached 776.3 S/cm at 773 K, which was fourfold higher than that of pure ZnO. This enhancement in electrical conductivity played a key role in improving the power factor (PF) of TE materials. The power factor for the Bi-doped ZnO film was enhanced to 463.8 μW/mK2 at 773 K compared to pristine ZnO (314.8 μW/mK2 ) under the same conditions.